The Verse-Line as a Whole Unit in Working Memory, Ease of Processing, and the Aesthetic Effects of Form. (3rd October 2014) - Fabb, Nigel
<x content-type="archive" xml:space="preserve">Abstract</x> Verse is text which is divided into lines. In this paper I explore a psychological account of how verse is processed, and specifically the hypothesis that the text is processed line by line, such that each line is held as a whole sequence in the limited capacity of working memory. I will argue that because the line is processed in this way, certain low-level aesthetic effects are thereby produced, thus giving a partial explanation for why verse is often a highly valued type of verbal behaviour. The general goal is to address the question of what literary form is, from a psychological perspective, and how the textual presence and psychological processing of form can contribute to particular aspects of the aesthetic experience of verse.